1998
DOI: 10.1093/jxb/49.325.1329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salt stress on growth, photosynthesis and nitrogen fixation in chick-pea (Cicer arietinum L.)

Abstract: utes is more a consequence of damage produced by salt stress than of a protective strategy. Plants of chick-pea (Cicer arietinum L. cv. ILC1919) inoculated with Mesorhizobium ciceri strain ch-191 Key words: Chick-pea, salt stress, nitrogen fixation, photowere grown in a controlled environmental chamber, synthesis, ammonium assimilation. and were administered salt (0, 50, 75, and 100 mM NaCl) during the vegetative period. Four harvests (4, 7, 11, and 14 d after treatment) were analysed. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(82 citation statements)
references
References 44 publications
11
70
0
1
Order By: Relevance
“…A strong correlation between sugar accumulation and osmotic stress tolerance has been widely reported (Gilmour et al 2000;Streeter et al 2001;Taji et al 2002), which support a higher tolerance of L. japonicus nodules to salt stress. M. truncatula nodules did not show nodule carbohydrate accumulation; however, amino acids accumulated in these nodules by NaCl, which could be explained as a consequence of damage produced by saline stress, in accordance with results of Gordon et al (1997), Soussi et al (1998) and Khadri et al (2007) in nodules of soybean, chickpea and common bean, respectively.…”
Section: Lo´pez and C Lluchsupporting
confidence: 86%
See 3 more Smart Citations
“…A strong correlation between sugar accumulation and osmotic stress tolerance has been widely reported (Gilmour et al 2000;Streeter et al 2001;Taji et al 2002), which support a higher tolerance of L. japonicus nodules to salt stress. M. truncatula nodules did not show nodule carbohydrate accumulation; however, amino acids accumulated in these nodules by NaCl, which could be explained as a consequence of damage produced by saline stress, in accordance with results of Gordon et al (1997), Soussi et al (1998) and Khadri et al (2007) in nodules of soybean, chickpea and common bean, respectively.…”
Section: Lo´pez and C Lluchsupporting
confidence: 86%
“…Shoot growth was more extensively affected than root growth in L. japonicus plants, consequently increases of root to shoot ratio with NaCl in L. japonicus plants are observed. Similar results have been detected in other legumes such as Cicer arietinum (Soussi et al 1998) and Phaseolus vulgaris (Khadri et al 2006), where the authors considered this behaviour profitable since it could improve plant water status by increasing the root requirements to explore a higher soil volume. The specific nitrogenase activity (mmol H 2 g (1 ) decreased from the vegetative (0 DAT) to the fructification stage (28 DAT) in nodules of both legumes; however, the nodular mass (data not shown) augmented in this period, by which the total nitrogenase activity (mmol H 2 plant (1 ) did not decrease in the same extend, supplying fixed nitrogen for the plant growth.…”
Section: Lo´pez and C Lluchsupporting
confidence: 79%
See 2 more Smart Citations
“…In the present study, other than floral characters, higher corm weight and corm diameter were observed in the bio-primed corms, whereas a decreased corm weight and corm diameter were found in untreated control. An overall reduction in control under salt stress was earlier observed by Soussi et al (1998). This reduction in weight of plants under stress may be due to the inhibition or hydrolysis of reserved food and its translocation to growing shoot portion (Singh et al 2008).…”
Section: Discussionmentioning
confidence: 80%